2005
DOI: 10.1021/ol051170p
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Fluorous Partition Coefficients by Solvent Tuning

Abstract: Low partition coefficients of fluorous components have been a persistent problem in liquid-liquid separations using perfluoroalkanes as the fluorous phase. Solvent tuning of both the nonfluorous and the fluorous phase dramatically enhances the partitioning of light or polar fluorous molecules into the fluorous liquid phase, while minimally effecting partition coefficients of nonfluorous molecules. These findings suggest an expanded scope for liquid-based separations in fluorous biphasic catalysis, fluorous-tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…In contrast, lightly fluorous compounds, such as HFUA, cannot be extracted into fluorous solvents, such as perfluoroalkanes [i.e., tetradecafluorohexane (TDFH), perfluoromethylcyclohexane, and so on], because of their low solubility. However, Curran et al reported that the solubility of lightly fluorous compounds was improved by "solvent tuning", which involves increasing the polarity of fluorous solvents by the addition of polar fluorous solvents, such as hydrofluoroethers, to perfluoroalkanes [31,32]. In this method, when solvent tuning was performed by adding perfluoroalcohol, 1H,1H,2H,2H-tridecafluoro-1-n-octanol (TFO), to TDFH, extraction of ion-pair forms between the nucleotides and HFUA could be performed.…”
Section: Selective Fluorous Biphasic Extraction For Nucleotides Withomentioning
confidence: 99%
“…In contrast, lightly fluorous compounds, such as HFUA, cannot be extracted into fluorous solvents, such as perfluoroalkanes [i.e., tetradecafluorohexane (TDFH), perfluoromethylcyclohexane, and so on], because of their low solubility. However, Curran et al reported that the solubility of lightly fluorous compounds was improved by "solvent tuning", which involves increasing the polarity of fluorous solvents by the addition of polar fluorous solvents, such as hydrofluoroethers, to perfluoroalkanes [31,32]. In this method, when solvent tuning was performed by adding perfluoroalcohol, 1H,1H,2H,2H-tridecafluoro-1-n-octanol (TFO), to TDFH, extraction of ion-pair forms between the nucleotides and HFUA could be performed.…”
Section: Selective Fluorous Biphasic Extraction For Nucleotides Withomentioning
confidence: 99%
“…It utilizes a fluorous phase to extract fluorous molecules from an organic or aqueous solvent [38]. FLLE has been used in biphasic catalysis and small molecule synthesis.…”
Section: Fluoroalkyl Tag Thioureamentioning
confidence: 99%
“…1. These include two hydrofluoro ethers, which may offer environmental advantages [2][3][4][5]. It is also important to emphasize that perfluoroarenes and similar unsaturated compounds are not fluorous.…”
Section: Introductionmentioning
confidence: 99%
“…The average CF 2 -CF 2 -CF 2 -CF 2 torsion angle was 167. 2 , with the F-CF 2 -CF 2 -F torsion angles generally falling into two regimes, ca. [40][41][42][43][44][45][46][47][48][49][50] and ca.…”
Section: Introductionmentioning
confidence: 99%